1970
DOI: 10.3329/bjb.v40i1.8004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of naphthalene acetic acid on yield attributes and yield of two varieties of rice (<i>Oryza sativa</i> L.)

Abstract: Effects of 100 and 200 ppm of naphthalene acetic acid (NAA) on yield attributes and yield of two varieties of rice during 2009 -2010 Boro season were evaluated. The highest plant height was observed due to 200 ppm in both BRRI dhan-29 (V 1 ) and BRRI dhan-50 (V 2 ). Number of tillers per plant were found to increase due to 100 ppm NAA only in BRRI dhan-29 and varied non-significantly. Yield attributes, viz. number of branches per panicle, number of grains per panicle and filled grains per panicle increased in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 3 publications
3
15
0
Order By: Relevance
“…On the other hand, the lowest length of fruit was produced by Manik with 0 ppm IAA treated plots (4.57 cm) which was followed by the treatment combinations of BARI Tomato-7 × 0 ppm IAA (4.72 cm) and Ratan × 200 ppm IAA (4.83 cm). Abdel et al (1996) showed that due to application of IAA and GA 3 increased flux seed yield due to increased length of fruit, this result also supported by Adam et al (2011) who also found that the naphthalene acetic acid increased yield of two varieties of rice (Oryza sativa L.) for increasing length of caryopsis.…”
Section: Length Of Fruitsupporting
confidence: 69%
See 2 more Smart Citations
“…On the other hand, the lowest length of fruit was produced by Manik with 0 ppm IAA treated plots (4.57 cm) which was followed by the treatment combinations of BARI Tomato-7 × 0 ppm IAA (4.72 cm) and Ratan × 200 ppm IAA (4.83 cm). Abdel et al (1996) showed that due to application of IAA and GA 3 increased flux seed yield due to increased length of fruit, this result also supported by Adam et al (2011) who also found that the naphthalene acetic acid increased yield of two varieties of rice (Oryza sativa L.) for increasing length of caryopsis.…”
Section: Length Of Fruitsupporting
confidence: 69%
“…Abdel et al (1996) showed that due to application of IAA and GA 3 increased flux seed yield and their metabolic constituents. Adam et al (2011) also found that the naphthalene acetic acid increased yield of two varieties of rice (Oryza sativa L.). Sanyal (1995) also found that application of plant growth regulator at vegetative stage increased fruit yield per hectare of tomato.…”
Section: Yield Hectare -1mentioning
confidence: 95%
See 1 more Smart Citation
“…This might help to increase the productivity of tillers. Another report also showed that, tiller production did not significantly differ using 100 ppm and 200 ppm NAA plant hormone (Adam et al, 2011).…”
Section: Resultsmentioning
confidence: 89%
“…In Bangladesh, reports regarding the effect of NAA on growth, yield and yield attributes of rice are available. Adam and Jahan (2011) reported that in BRRI dhan 29, yield and yield attributes increased following 100 and 200 ppm NAA application, whereas, most of the yield parameters decreased in BRRI dhan 50. In a comparative growth analysis, Jahan and Adam (2011) observed differences in responses between two varieties of rice and between the two concentrations of NAA where, better stimulation was due to 100 ppm.…”
Section: Introductionmentioning
confidence: 96%